EFFECTS OF REAR PLANFORM CROPPING CONFIGURATION ON WING-IN-GROUND CRAFT - Damian Raven Dewantara; I Ketut Aria Pria Utama (Journal of Marine-Earth Science and Technology, 2025)
Emissions from the global transportation sector represent a significant environmental challenge, with high-speed maritime transport being a notable contributor. The reduction of fuel consumption is therefore a critical objective in the development of future marine vehicles. The Wing-in-Ground (WIG) craft, an innovative transport modality developed since the mid-twentieth century, operates by utilising the aerodynamic ground effect to achieve aircraft-like speeds with substantially lower power requirements. This makes it a promising solution for efficient, high-speed maritime transit. A key innovation in WIG design is the Lippisch-style cropped reverse delta wing, a configuration known to enhance aerodynamic performance. To optimize this design, an investigation into the effects of rear planform cropping is required. This study employs computational fluid dynamics (CFD), utilising a Reynolds-Averaged Navier-Stokes (RANS) solver, to perform analysis of WIG models with various rear planform cropping configurations. The investigation covers trailing edge crop percentages of 0%, 10%, 20%, and 30% of the root chord. The results demonstrate that higher cropping percentages positively impact aerodynamic performance.